Task Based English Language Teaching in Saudi Intermediate Schools - Al Muhaimeed, Sultan A. (Widya Mandala Catholic University Surabaya, 2015)
This study investigates the effectiveness and appropriateness of a constructivist instructional practice for EFL. It strives to determine whether adopting Task-Based Language Teaching (TBLT) is a more effective means to increase students’ reading comprehension when compared to that of the traditional teaching method. It also attempts to gain understandings that accompany TBLT implementation through constant comparison and contrast them with those that accompany the traditional teaching method. The mixed-method study covers quasi-experimental approach that uses one pretest and several posttests to collect quantitative data, as well as classroom observation and researcher log to collect qualitative data. The independent variable is the use of TBLT and the dependent variable is the students’ reading comprehension achievement scores. A Two-Factor Split Plot analysis with pretest as the covariate is used for analyzing the quantitative data. The analysis of qualitative data includes synthesis, rich, and detailed descriptions for classroom observation and grounded theory for researcher log data. Keywords: Task Based Language Teaching, Constructivist Instructional Practices